Biosynthesis and tissue-specific partitioning of camphor and eugenol in Ocimum kilimandscharicum - Singh, Priyanka; Kalunke, Raviraj M.; Shukla, Anurag; Tzfadia, Oren; Thulasiram, V. Hirekodathakallu; Giri, Ashok P. (Phytochemistry, 2020)
In Ocimum kilimandscharicum, the relative volatile composition of camphor in leaves was as high as 55%, while that of eugenol in roots was 57%. These metabolites were differentially partitioned between the aerial and root tissues. Global metabolomics revealed tissue-specific biochemical specialization, evident by the differential distribution of 2588 putative metabolites across nine tissues. Next-generation sequencing analysis indicated differential expression of 51 phenylpropanoid and 55 terpenoid pathway genes in aerial and root tissues. By integrating metabolomics with transcriptomics, the camphor biosynthesis pathway in O. kilimandscharicum was elucidated. In planta bioassays revealed the role of geranyl diphosphate synthase (gpps) and borneol dehydrogenase (bdh) in camphor biosynthesis. Further, the partitioning of camphor was attributed to tissue-specific gene expression of both the pathway entry point (gpps) and terminal (bdh) enzyme. Unlike camphor, eugenol accumulated more in roots; however, absence of the eugenol synthase gene in roots indicated long distance transport from aerial tissues. In silico co-expression analysis indicated the potential involvement of ATP-binding cassette, multidrug and toxic compound extrusion, and sugar transporters in eugenol transport. Similar partitioning was evident across five other Ocimum species. Overall, our work indicates that metabolite partitioning maybe a finely regulated process, which may have implications on plant growth, development, and defense.
Keywords: Borneol dehydrogenase; Camphor; Eugenol; Geranyl diphosphate synthase; Lamiaceae; Metabolite partitioning; Metabolomics; Ocimum kilimandscharicum; Transcriptomics